Edukasi Gout Arthritis dan Senam Ergonomik untuk Meningkatkan Pengetahuan Serta Kesehatan Lansia di Panti Wening Wardoyo Ungaran - Al Hajar Fuadatus Zurroh; Melati Aprilliana Ramadhani; Ika Nilawati; Dwi Retna Susilowati (UNIVERSITAS NGUDI WALUYO, 2025)
Gout Arthritis is a form of arthritis that often occurs in the elderly, especially due to an unhealthy lifestyle and lack of physical activity. Health education and physical interventions such as ergonomic exercises can be effective strategies to improve the understanding and health conditions of the elderly. This community service activity aims to provide education about Gout Arthritis and ergonomic exercises in improving the knowledge and health of the elderly at Panti Wening Wardoyo, Ungaran. A total of 48 elderly people participated in educational activities and ergonomic exercise practices. Participants' knowledge was measured using a multiple choice question instrument before (pretest) and after (posttest) the intervention. The pretest results showed that 8.33% of participants were in the